2022
DOI: 10.3390/life13010057
|View full text |Cite
|
Sign up to set email alerts
|

Tare Soil Disinfestation from Cyst Nematodes Using Inundation

Abstract: The dissemination of soil tares in the potato and sugar beet processing industry is one of the main paths for the spread of potato cyst nematodes (PCN), a severe quarantine pest. Efficient measures for the disinfestation of tare soil from PCN, but also from beet cyst nematodes (BCN), are needed. In our study, Globodera pallida (a PCN) and Heterodera schachtii (a BCN) cysts were sealed in gauze bags and imbedded in sedimentation basins. The cysts were either placed a) in a presedimentation basin (Brukner basin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Inundation has proven an effective eradication strategy, with loss of viability of PCN cyst content (Runia et al, 2014). Nevertheless, non-viable cysts were still isolated after inundation (Berger et al, 2023;Runia et al, 2014). The use of resistant potato varieties in infested fields has been used with high success to eradicate G. rostochiensis (Price et al, 2021;de Boer et al, 2021;Gartner et al, 2021;Mwangi et al, 2021;Orlando & Boa, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Inundation has proven an effective eradication strategy, with loss of viability of PCN cyst content (Runia et al, 2014). Nevertheless, non-viable cysts were still isolated after inundation (Berger et al, 2023;Runia et al, 2014). The use of resistant potato varieties in infested fields has been used with high success to eradicate G. rostochiensis (Price et al, 2021;de Boer et al, 2021;Gartner et al, 2021;Mwangi et al, 2021;Orlando & Boa, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Inundation has proven an effective eradication strategy, with loss of viability of PCN cyst content(Runia et al, 2014). Nevertheless, non-viable cysts were still isolated after inundation(Runia et al, 2014;Berger et al, 2023). The use of resistant potato varieties in infested elds has been used with high success to eradicate G. rostochiensis(Price et al., 2020; de Boer et al, 2021; Gartner et al, 2021; Mwangi et al, 2021; Orlando & Boa, 2023).…”
mentioning
confidence: 99%
“…The activation of specific microbial activity and the release of other nematicidal compounds may contribute to RKN-soil suppressiveness at the strawberry farms [ 11 ]. Berger and colleagues [ 12 ] found that the inundation process of two types of tare soils (namely sedimentation basins and the Brukner basin) during sugar beet processing efficiently decreased the viability of G. pallida and H. schachtii under laboratory-controlled conditions. These findings offer promising strategies for eco-friendly PPN control in agriculture.…”
mentioning
confidence: 99%